2017
DOI: 10.1038/s41598-017-00773-w
|View full text |Cite
|
Sign up to set email alerts
|

Higher dietary intakes of choline and betaine are associated with a lower risk of primary liver cancer: a case-control study

Abstract: The dietary intake of methyl donors is favorably associated with many diseases, but the findings regarding primary liver cancer (PLC) risk are limited. This study investigated the association between the intake of choline, betaine and methionine and PLC risk in adults. This 1:1 matched case-control study enrolled 644 hospital-based PLC patients and 644 community-based controls who were matched by sex and age, in Guangzhou, China. An interviewer-administered questionnaire and a food-frequency questionnaire were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 48 publications
4
32
0
Order By: Relevance
“…As an osmolyte, betaine increases the water retention of cells, replaces inorganic salts, and protects against osmotic shocks [35]. Betaine has been used with good results in a variety of experimental disease models, including AGA, alcohol liver disease, nonalcoholic fatty liver disease, obesity, diabetes and multiple sclerosis [15,24,25,[36][37][38][39][40][41][42][43][44]. Although its mechanism of action is not fully understood, it is suggested to act primarily as methyl donor in several metabolic reactions, or to influence epigenetic marks.…”
Section: Discussionmentioning
confidence: 99%
“…As an osmolyte, betaine increases the water retention of cells, replaces inorganic salts, and protects against osmotic shocks [35]. Betaine has been used with good results in a variety of experimental disease models, including AGA, alcohol liver disease, nonalcoholic fatty liver disease, obesity, diabetes and multiple sclerosis [15,24,25,[36][37][38][39][40][41][42][43][44]. Although its mechanism of action is not fully understood, it is suggested to act primarily as methyl donor in several metabolic reactions, or to influence epigenetic marks.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have reported that when deprived of choline, varying degrees of liver damage and liver diseases developed, including elevated transaminases [11], affected lipid metabolism and transport [12], fatty liver [13], liver cirrhosis [13] and even liver cancer [14], whereas choline or betaine supplementation ameliorated liver damage [15,16], and choline supplementation increased global DNA methylation and DNA methyltransferase expression in HepG2 cells [17], which implied that choline or betaine might not only be associated with hepatocarcinogenesis, but also with liver cancer survival. To date, although scarcely, three case control studies [18][19][20] have evaluated the relationship between choline and betaine and human liver cancer risk, in which consistently favorable effects of choline were found. Of note, previous studies reported seriously insufficient dietary choline intake in Chinese population [20,21], and approximately 50% of the total HCC cases occurred in China [19].…”
Section: Introductionmentioning
confidence: 99%
“…To date, although scarcely, three case control studies [18][19][20] have evaluated the relationship between choline and betaine and human liver cancer risk, in which consistently favorable effects of choline were found. Of note, previous studies reported seriously insufficient dietary choline intake in Chinese population [20,21], and approximately 50% of the total HCC cases occurred in China [19]. No existing studies have reported the associations between choline and betaine and liver cancer survival, it would be a very meaningful topic to investigate the influence of choline and betaine status on HCC prognosis in Chinese population.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that betaine has many pharmacological functions, such as antioxidant and antiin ammatory effects [20,21]. A retrospective study suggested that higher betaine intake may be related to a lower risk of primary liver cancer [22]. There is a favorable relationship between the blood betaine concentration and the severity of nonalcoholic fatty liver disease (NAFLD) in community-based participants [23].…”
Section: Introductionmentioning
confidence: 99%